Technological and Institutional Innovations for Marginalized Smallholders in Agricultural Development 2016
DOI: 10.1007/978-3-319-25718-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Yield-Increasing Crop Technologies on Productivity and Poverty in Two Districts of Ethiopia

Abstract: Ethiopian agriculture is characterized by low productivity which has contributed to the persistence of food insecurity and poverty in the country. Reports indicate that several yield-increasing technologies are available but have not yet been adequately utilized. This chapter assesses the potential impact of yieldincreasing crop technologies on productivity and poverty based on the data collected from two districts in Ethiopia. We focus on the use of improved seeds, together with appropriate agronomic packages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…However, considering the overall grain performance from Samsorg 42 variety, the various components of yields estimated contributed immensely towards this higher total grain yield by the crop variety. This report is in line with those of Kotu & Admassie (2015); Staggenborg (2016); Msongaleli et al (2017) and Mwamahonje & Maseta (2018), who observed high grain yield of sorghum varieties due to genes and the environmental conditions which prevailed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, considering the overall grain performance from Samsorg 42 variety, the various components of yields estimated contributed immensely towards this higher total grain yield by the crop variety. This report is in line with those of Kotu & Admassie (2015); Staggenborg (2016); Msongaleli et al (2017) and Mwamahonje & Maseta (2018), who observed high grain yield of sorghum varieties due to genes and the environmental conditions which prevailed.…”
Section: Discussionsupporting
confidence: 91%
“…These varieties differ significantly in panicle length and number of grainspanicle -1 , which can be attributed to the plant's genetic makeup and environment. Kotu & Admassie (2015); Staggenborg (2016) and Msongaleli et al (2017) reported that head length is a primary factor of grain production. Omoregie & Nwajei (2015) and Nwajei et al (2019) reported that millet varieties with longer panicles had a higher number of grains.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that focus on agriculture and welfare issues evidenced that adopting improved agricultural innovations and technologies can reduce poverty and food insecurity and increases farm household incomes and overall social welfare [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. Many studies have also replicated, extended, and explored the impact of adopting agricultural technologies in different parts of the globe.…”
Section: Introductionmentioning
confidence: 99%